(untitled) (Annals of Medical Research, 2021)
Aim: Hereditary breast cancer is one of the components of hereditary breast-over cancer syndrome (HBOC) that results with multiple cancer predisposition. Heterozygous mutations of BRCA1 and BRCA2 that have crucial roles in DNA repair are responsible for about 12-25% of the patients. 25 different genes have been identified to be a causal factor in the patients whose BRCA tests are negative. Most of these genes are involved in functionally related genome maintenance pathways with BRCA1 and BRCA2. We aimed to investigate genes other than BRCA1/2 to determine breast cancer etiology. Materials and Methods: Of the 230 patients diagnosed with breast cancer, 38 patients with no mutation in BRCA1 / 2 were evaluated. Hereditary breast cancer panel was designed with QIAseq solution. The sequencing process was performed on the Illumina MiSeq system. The data analyses were performed on QIAGEN Clinical Insight analyze software. Results: The genes associated with hereditary breast cancer were studied with the new generation sequencing method in 38 of the patients without pathogenic or VUS variants. Pathogenic/likely pathogenic variants were detected in 3 (7.8%) of 38 patients, while VUS was detected in 10 (26.3%) patients. Of these 22 genes, c.312C A (p.Tyr90Ter) in MUTY, c.1225C T (p.Arg409Trp) in STK11, c.1690C T (p.Gln564Ter) variant in BARD1 interpreted as pathogenic.Conclusion: Our data provide insight into the genetics of HBOC syndrome in Turkey. These studies will help to improve the clinical management and better risk assessment of hereditary breast and ovarian cancer.